Takhrij and Syarah Hadith of Agrotechnology: Content and Benefits of Black Cumin - Ilmi Nurkarimah; Wahyudin Darmalaksana; Taufik Rahman; Anna Aina Roosda (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith with regard to agrotechnology. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The results and discussion of this research is about takhrij and syarah hadith regarding the content and benefits of black cumin (Black Seed). Black cumin (Black Seed) is known to have many benefits with chemical content in the form of vegetable fats and oils (35%), carbohydrates (32%), protein (21%), water (5%), saponins, nigelin, and other ingredients (7%). Some other ingredients in black cumin (Black Seed) that have great benefits are nigelone crystals, arganine, fatty acids, carotene, amino acids, minerals, and vitamins.